2021
DOI: 10.3904/kjim.2019.413
|View full text |Cite
|
Sign up to set email alerts
|

L-carnitine treatment attenuates renal tubulointerstitial fibrosis induced by unilateral ureteral obstruction

Abstract: Background/Aims: Accumulating evidence indicates that L-carnitine (LC) protects against multiorgan damage through its antioxidant properties and preservation of the mitochondria. Little information is available about the effects of LC on renal fibrosis. This study examined whether LC treatment would provide renoprotection in a rat model of unilateral ureteral obstruction (UUO) and in vitro. Methods: Sprague-Dawley rats that underwent UUO were treated daily with LC for 7 or 14 days. The influence of LC on renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Zhao et al . stated that L-carnitine use was accompanied by amelioration of renal inflammation-induced via unilateral ureteral obstruction through inhibition of pro-inflammatory cytokines and attenuation of tubulointerstitial inflammation in rats ( 39 ). Moreover, L-carnitine; in one study; was able to improve renal function and mitigate histological abnormalities in rats suffering from chronic kidney disease ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al . stated that L-carnitine use was accompanied by amelioration of renal inflammation-induced via unilateral ureteral obstruction through inhibition of pro-inflammatory cytokines and attenuation of tubulointerstitial inflammation in rats ( 39 ). Moreover, L-carnitine; in one study; was able to improve renal function and mitigate histological abnormalities in rats suffering from chronic kidney disease ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…This concept is supported by studies that used antioxidant drugs or genetic knockout of cyclooxygenase-2 [ 18 ]. In addition, we and others have reported a relation between mitochondria and oxidative stress because mitochondria play canonical roles in cellular respiration and oxidative phosphorylation, and are a major source of ROS [ 19 ]. The finding herein that RIP inhibitors or ICG-001 can regulate the expression of oxidant and antioxidant enzymes, decrease ROS production, and balance mitochondria-controlling genes suggests that they may be able to protect mitochondrial morphological integrity.…”
Section: Discussionmentioning
confidence: 99%
“…87 The metabolic transition of renal fibroblasts from oxidative phosphorylation to aerobic glycolysis (Warburg effect) activates fibroblasts, whereas the inhibition of aerobic glycolysis in renal fibroblasts can significantly reduce RF. 88 KEGG pathway analysis showed that the pathways enriched among the target genes of the DE-miRNAs, including the ErbB, VEGF and TNF signalling pathways, are related to cardiomyocyte fibrosis and renal fibrosis, diabetic nephropathy and chronic renal failure, 89,90 along with apoptosis, glycerophospholipid metabolism, pyrimidine metabolism, tryptophan metabolism and glutamate metabolism, 91–94 all of which are related to renal interstitial fibrosis. GO enrichment analysis of the DE-miRNA target genes further showed that these genes are significantly associated with metabolic processes.…”
Section: Discussionmentioning
confidence: 99%